Nerve regeneration therapy and its application in the field of oral and maxillofacial surgery - Subramaniam, Pram Kumar (Episirus Scientifica, 2020)
In oral and maxillofacial surgical discipline context; neurological injury often occurs to the trigeminal nerve as well as facial nerve caused by trauma, pathology, infection, inflammatory, and other orofacial surgical procedures. Most attention has been devoted to the inferior alveolar nerve and lingual nerve as these nerves are commonly involved in routine dental procedures such as anesthetics block, root canal therapy, dental implant surgery and surgical removal of third molars or wisdom tooth. Side effect of these injuries ranges from anaesthesia, dysesthesia, paresthesia, facial paresis and even paralysis. Various surgical and non-surgical options are available to treat the above said conditions in order to allow repair and regeneration of the peripheral branches of facial and trigeminal nerves so as to improve the quality of life for patients. Surgical options include direct primary repair such neurorrhaphy via end-to-end approximation, biological and synthetic conduit-based guided regeneration or graft bridging and even coaptation. Non-surgical treatment is used as means to facilitate faster nerve end growth or axonal regeneration such as protein therapy, laser phototherapy and low frequency electric stimulation therapy. This presentation attempts to discuss the use of different options of nerve regeneration therapy and its relevance in the field of oral and maxillofacial surgery.